Superconducting NbN thin films for use in superconducting radio frequency cavities. (11th January 2021) - Leith, S; Vogel, M; Fan, J; Seiler, E; Ries, R; Jiang, X
Abstract: In recent years, renewed interest has been given to alternatives to bulk Nb for use in superconducting radio frequency (SRF) cavities. Much of this research has involved the use of thin films of Nb or other alternative high T c materials. Given the recent insights into the potential of single layer high − κ materials and the prospective performance improvements due to the use of multilayer (ML) superconductor–insulator–superconductor (SIS) film structures, NbN stands as a potential candidate for use in future accelerating cavities. Much of the research completed thus far has focused on the deposition of NbN onto single crystal substrates such as Si and MgO, or onto bulk Nb. In this study, the deposition of high T c NbN thin films onto copper substrates, in the form of both single layers and as part of an ML SIS structure, using DC magnetron sputtering (DC MS) was explored. The effects of the deposition parameters on the film microstructure and superconducting properties of the NbN films as well as the challenges involved in depositing ML SIS films onto copper substrates are reported on. A maximum T c = 16.1 K has been achieved for single layer NbN films, as determined by AC susceptometry measurements. Initial results for the SIS film structures, deposited onto copper in the form of Nb/AlN/NbN, have also shown an enhancement in the first magnetic flux entry field value above that achieved by a single Nb layer. This enhancement has been found to be highly dependent on the quality of the SIS film coatings.